"Philosophical faith” and mystical experience: Convergence and divergence - Duplinskya, Yuliya Mikhailovna; Friauf, Vasily Aleksandrovich (Известия Саратовского университета: Новая серия. Серия Философия. Психология. Педагогика, 2022)
Introduction. The common version that mystical experience reveals the deep unity of religious traditions, hiding behind the external facade of their diff erences, seems controversial. Theoretical analysis. It is justifi ed that the similarity between diff erent traditions of mysticism does not express the quintessence of religiosity, as such, but onlyconvergence in a certain phase of the evolution of religions. Mysticism is compared with the entry of religion into the phenomenological phase of development. Mysticism, like philosophical phenomenology, is turned to the experience of consciousness. Phenomenology forms the common space of meeting for mystical experience and the experience of philosophical faith. Phenomenological experience is similar to the “energy minimum” of mystical states. Like the state of heat death in thermodynamics, this is a kind of common denominator, at which all mystical traditions are aimed in the process of devolution, and then desacralization. After the mystical-phenomenological phase, religious consciousness is reoriented from the phenomenological Presence to the eschatological Coming. Here the trajectories of divergence are again indicated. Conclusion. From the standpoint of Orthodox ascetics, the philosophical faith, as a phenomenological version of mysticism, is insuffi cient, because it is associated only with a change in consciousness. The true experience of God’s message in Christianity requires the transformation of everything - including the fl esh of human nature.